# 11.11: A.11.3- Section 11.3 Answers

$$\newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} }$$

$$\newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}}$$

$$\newcommand{\id}{\mathrm{id}}$$ $$\newcommand{\Span}{\mathrm{span}}$$

( \newcommand{\kernel}{\mathrm{null}\,}\) $$\newcommand{\range}{\mathrm{range}\,}$$

$$\newcommand{\RealPart}{\mathrm{Re}}$$ $$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$

$$\newcommand{\Argument}{\mathrm{Arg}}$$ $$\newcommand{\norm}[1]{\| #1 \|}$$

$$\newcommand{\inner}[2]{\langle #1, #2 \rangle}$$

$$\newcommand{\Span}{\mathrm{span}}$$

$$\newcommand{\id}{\mathrm{id}}$$

$$\newcommand{\Span}{\mathrm{span}}$$

$$\newcommand{\kernel}{\mathrm{null}\,}$$

$$\newcommand{\range}{\mathrm{range}\,}$$

$$\newcommand{\RealPart}{\mathrm{Re}}$$

$$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$

$$\newcommand{\Argument}{\mathrm{Arg}}$$

$$\newcommand{\norm}[1]{\| #1 \|}$$

$$\newcommand{\inner}[2]{\langle #1, #2 \rangle}$$

$$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\AA}{\unicode[.8,0]{x212B}}$$

$$\newcommand{\vectorA}[1]{\vec{#1}} % arrow$$

$$\newcommand{\vectorAt}[1]{\vec{\text{#1}}} % arrow$$

$$\newcommand{\vectorB}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} }$$

$$\newcommand{\vectorC}[1]{\textbf{#1}}$$

$$\newcommand{\vectorD}[1]{\overrightarrow{#1}}$$

$$\newcommand{\vectorDt}[1]{\overrightarrow{\text{#1}}}$$

$$\newcommand{\vectE}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash{\mathbf {#1}}}}$$

$$\newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} }$$

$$\newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}}$$

$$\newcommand{\avec}{\mathbf a}$$ $$\newcommand{\bvec}{\mathbf b}$$ $$\newcommand{\cvec}{\mathbf c}$$ $$\newcommand{\dvec}{\mathbf d}$$ $$\newcommand{\dtil}{\widetilde{\mathbf d}}$$ $$\newcommand{\evec}{\mathbf e}$$ $$\newcommand{\fvec}{\mathbf f}$$ $$\newcommand{\nvec}{\mathbf n}$$ $$\newcommand{\pvec}{\mathbf p}$$ $$\newcommand{\qvec}{\mathbf q}$$ $$\newcommand{\svec}{\mathbf s}$$ $$\newcommand{\tvec}{\mathbf t}$$ $$\newcommand{\uvec}{\mathbf u}$$ $$\newcommand{\vvec}{\mathbf v}$$ $$\newcommand{\wvec}{\mathbf w}$$ $$\newcommand{\xvec}{\mathbf x}$$ $$\newcommand{\yvec}{\mathbf y}$$ $$\newcommand{\zvec}{\mathbf z}$$ $$\newcommand{\rvec}{\mathbf r}$$ $$\newcommand{\mvec}{\mathbf m}$$ $$\newcommand{\zerovec}{\mathbf 0}$$ $$\newcommand{\onevec}{\mathbf 1}$$ $$\newcommand{\real}{\mathbb R}$$ $$\newcommand{\twovec}[2]{\left[\begin{array}{r}#1 \\ #2 \end{array}\right]}$$ $$\newcommand{\ctwovec}[2]{\left[\begin{array}{c}#1 \\ #2 \end{array}\right]}$$ $$\newcommand{\threevec}[3]{\left[\begin{array}{r}#1 \\ #2 \\ #3 \end{array}\right]}$$ $$\newcommand{\cthreevec}[3]{\left[\begin{array}{c}#1 \\ #2 \\ #3 \end{array}\right]}$$ $$\newcommand{\fourvec}[4]{\left[\begin{array}{r}#1 \\ #2 \\ #3 \\ #4 \end{array}\right]}$$ $$\newcommand{\cfourvec}[4]{\left[\begin{array}{c}#1 \\ #2 \\ #3 \\ #4 \end{array}\right]}$$ $$\newcommand{\fivevec}[5]{\left[\begin{array}{r}#1 \\ #2 \\ #3 \\ #4 \\ #5 \\ \end{array}\right]}$$ $$\newcommand{\cfivevec}[5]{\left[\begin{array}{c}#1 \\ #2 \\ #3 \\ #4 \\ #5 \\ \end{array}\right]}$$ $$\newcommand{\mattwo}[4]{\left[\begin{array}{rr}#1 \amp #2 \\ #3 \amp #4 \\ \end{array}\right]}$$ $$\newcommand{\laspan}[1]{\text{Span}\{#1\}}$$ $$\newcommand{\bcal}{\cal B}$$ $$\newcommand{\ccal}{\cal C}$$ $$\newcommand{\scal}{\cal S}$$ $$\newcommand{\wcal}{\cal W}$$ $$\newcommand{\ecal}{\cal E}$$ $$\newcommand{\coords}[2]{\left\{#1\right\}_{#2}}$$ $$\newcommand{\gray}[1]{\color{gray}{#1}}$$ $$\newcommand{\lgray}[1]{\color{lightgray}{#1}}$$ $$\newcommand{\rank}{\operatorname{rank}}$$ $$\newcommand{\row}{\text{Row}}$$ $$\newcommand{\col}{\text{Col}}$$ $$\renewcommand{\row}{\text{Row}}$$ $$\newcommand{\nul}{\text{Nul}}$$ $$\newcommand{\var}{\text{Var}}$$ $$\newcommand{\corr}{\text{corr}}$$ $$\newcommand{\len}[1]{\left|#1\right|}$$ $$\newcommand{\bbar}{\overline{\bvec}}$$ $$\newcommand{\bhat}{\widehat{\bvec}}$$ $$\newcommand{\bperp}{\bvec^\perp}$$ $$\newcommand{\xhat}{\widehat{\xvec}}$$ $$\newcommand{\vhat}{\widehat{\vvec}}$$ $$\newcommand{\uhat}{\widehat{\uvec}}$$ $$\newcommand{\what}{\widehat{\wvec}}$$ $$\newcommand{\Sighat}{\widehat{\Sigma}}$$ $$\newcommand{\lt}{<}$$ $$\newcommand{\gt}{>}$$ $$\newcommand{\amp}{&}$$ $$\definecolor{fillinmathshade}{gray}{0.9}$$

1. $$C(x)=\frac{L^{2}}{3}+\frac{4L^{2}}{\pi ^{2}}\sum_{n=1}^{\infty}\frac{(-1)^{n}}{n^{2}}\cos\frac{n\pi x}{L}$$

2. $$C(x)=\frac{1}{2}+\frac{4}{\pi ^{2}}\sum_{n=1}^{\infty}\frac{1}{(2n-1)^{2}}\cos (2n-1)\pi x$$

3. $$C(x)=-\frac{2L^{2}}{3}+\frac{4L^{2}}{\pi ^{2}}\sum_{n=1}^{\infty}\frac{1}{n^{2}}\cos\frac{n\pi x}{L}$$

4. $$C(x)=\frac{1-\cos k\pi}{k\pi}-\frac{2k}{\pi}\sum_{n=1}^{\infty}\frac{[1-(-1)^{n}\cos k\pi}{n^{2}-k^{2}}\cos nx$$

5. $$C(x)=\frac{1}{2}-\frac{2}{\pi}\sum_{n=1}^{\infty}\frac{(-1)^{n}}{2n-1}\cos\frac{(2n-1)\pi x}{L}$$

6. $$C(x)=-\frac{2L^{2}}{3}+\frac{4L^{2}}{\pi ^{2}}\sum_{n=1}^{\infty}\frac{(-1)^{n}}{n^{2}}\cos\frac{n\pi x}{L}$$

7. $$C(x)=\frac{1}{3}+\frac{4}{\pi ^{2}}\sum_{n=1}^{\infty}\frac{1}{n^{2}}\cos n\pi x$$

8. $$C(x)=\frac{e^{\pi}-1}{\pi }+\frac{2}{\pi}\sum_{n=1}^{\infty}\frac{[(-1)^{n}e^{\pi}-1]}{(n^{2}+1)}\cos nx$$

9. $$C(x)=\frac{L^{2}}{6}-\frac{L^{2}}{\pi ^{2}}\sum_{n=1}^{\infty}\frac{1}{n^{2}}\cos\frac{2n\pi x}{L}$$

10. $$C(x)=-\frac{2L^{2}}{3}+\frac{4L^{2}}{\pi ^{2}} \sum_{n=1}^{\infty}\frac{1}{n^{2}}\cos\frac{n\pi x}{L}$$

11. $$S(x)=\frac{4}{\pi} \sum_{n=1}^{\infty}\frac{1}{(2n-1)}\sin\frac{(2n-1)\pi x}{L}$$

12. $$S(x)=\frac{2}{\pi} \sum_{n=1}^{\infty}\frac{1}{n}\sin n\pi x$$

13. $$S(x)=\frac{2}{\pi} \sum_{n=1}^{\infty}[1-(-1)^{n}\cos k\pi]\frac{n}{n^{2}-k^{2}}\sin nx$$

14. $$S(x)=\frac{2}{\pi} \sum_{n=1}^{\infty}\frac{1}{n}\left[1-\cos\frac{n\pi}{2}\right]\sin\frac{n\pi x}{L}$$

15. $$S(x)=\frac{4L}{\pi ^{2}} \sum_{n=1}^{\infty}\frac{(-1)^{n+1}}{(2n-1)^{2}}\sin\frac{(2n-1)\pi x}{L}$$

16. $$S(x)=\frac{\pi}{2}\sin x-\frac{16}{\pi} \sum_{n=1}^{\infty}\frac{n}{(4n^{2}-1)^{2}}\sin 2nx$$

17. $$S(x)=-\frac{2}{\pi} \sum_{n=1}^{\infty}\frac{n[(-1)^{n}e^{\pi}-1]}{(n^{2}+1)}\sin nx$$

18. $$C_{M}(x)=-\frac{4}{\pi} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{2n-1}\cos\frac{(2n-1)\pi x}{2L}$$

19. $$C_{M}(x)=-\frac{4L^{2}}{\pi} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{2n-1}\left[1-\frac{8}{(2n-1)^{2}\pi ^{2}}\right]\cos\frac{(2n-1)\pi x}{2L}$$

20. $$C_{M}(x)=-\frac{4}{\pi} \sum_{n=1}^{\infty}\left[ (-1)^{n}+\frac{2}{(2n-1)\pi}\right]\cos\frac{(2n-1)\pi x}{2}$$

21. $$C_{M}(x)=-\frac{4}{\pi} \sum_{n=1}^{\infty}\frac{1}{2n-1}\cos\frac{(2n+1)\pi}{4}\cos\frac{(2n-1)\pi x}{2L}$$

22. $$C_{M}(x)=\frac{4}{\pi} \sum_{n=1}^{\infty}(-1)^{n}\frac{2n-1}{(2n-3)(2n+1)}\cos\frac{(2n-1)x}{2}$$

23. $$C_{M}(x)=-\frac{8}{\pi} \sum_{n=1}^{\infty}\frac{1}{(2n-3)(2n+1)}\cos\frac{(2n-1)x}{2}$$

24. $$C_{M}(x)=-\frac{8L^{2}}{\pi ^{2}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{2}}\left[1+\frac{4(-1)^{n}}{(2n-1)\pi}\right]\cos\frac{(2n-1)\pi x}{2L}$$

25. $$S_{M}(x)=\frac{4}{\pi} \sum_{n=1}^{\infty}\frac{1}{(2n-1)}\sin\frac{(2n-1)\pi x}{2L}$$

26. $$S_{M}(x)=-\frac{16L^{2}}{\pi ^{2}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{2}}\left[ (-1)^{n}+\frac{2}{(2n-1)\pi}\right]\sin\frac{(2n-1)\pi x}{2L}$$

27. $$S_{M}(x)=\frac{4}{\pi} \sum_{n=1}^{\infty}\frac{1}{2n-1}\left[ 1-\cos\frac{(2n-1)\pi }{4}\right]\sin\frac{(2n-1)\pi x}{2L}$$

28. $$S_{M}(x)=\frac{4}{\pi} \sum_{n=1}^{\infty}\frac{2n-1}{(2n-3)(2n+1)}\sin\frac{(2n-1)x}{2}$$

29. $$S_{M}(x)=\frac{8}{\pi} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{(2n-3)(2n+1)}\sin\frac{(2n-1)x}{2}$$

30. $$S_{M}(x)=\frac{8L^{2}}{\pi ^{2}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{2}}\left[(-1)^{n}+\frac{4}{(2n-1)\pi}\right]\sin\frac{(2n-1)\pi x}{2L}$$

31. $$C(x)=-\frac{7L^{4}}{5}-\frac{144L^{4}}{\pi ^{4}} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{n^{4}}\cos\frac{n\pi x}{L}$$

32. $$C(x)=-\frac{2L^{4}}{5}-\frac{48L^{4}}{\pi ^{4}} \sum_{n=1}^{\infty}\frac{1+(-1)^{n}2}{n^{4}}\cos\frac{n\pi x}{L}$$

33. $$C(x)=\frac{3L^{4}}{5}-\frac{48L^{4}}{\pi ^{4}} \sum_{n=1}^{\infty}\frac{2+(-1)^{n}}{n^{4}}\cos\frac{n\pi x}{L}$$

34. $$C(x)=\frac{L^{4}}{30}-\frac{3L^{4}}{\pi ^{4}} \sum_{n=1}^{\infty}\frac{1}{n^{4}}\cos\frac{2n\pi x}{L}$$

36. $$S(x)=\frac{8L^{2}}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\sin\frac{(2n-1)\pi x}{L}$$

37. $$S(x)=-\frac{4L^{3}}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{(1+(-1)^{n}2)}{n^{3}}\sin\frac{n\pi x}{L}$$

38. $$S(x)=-\frac{12L^{3}}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{n^{3}}\sin\frac{n\pi x}{L}$$

39. $$S(x)=\frac{96L^{4}}{\pi ^{5}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{5}}\sin\frac{(2n-1)\pi x}{L}$$

40. $$S(x)=-\frac{720L^{5}}{\pi ^{5}} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{n^{5}}\sin\frac{n\pi x}{L}$$

41. $$S(x)=-\frac{240L^{5}}{\pi ^{5}} \sum_{n=1}^{\infty}\frac{1+(-1)^{n}2}{n^{5}}\sin\frac{n\pi x}{L}$$

43. $$C_{M}(x)=-\frac{64L^{3}}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\left[(-1)^{n}+\frac{3}{(2n-1)\pi}\right]\cos\frac{(2n-1)\pi x}{2L}$$

44. $$C_{M}(x)=-\frac{32L^{2}}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{(2n-1)^{3}}\cos\frac{(2n-1)\pi x}{2L}$$

45. $$C_{M}(x)=-\frac{96L^{3}}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\left[(-1)^{n}+\frac{2}{(2n-1)\pi}\right]\cos\frac{(2n-1)\pi x}{2L}$$

46. $$C_{M}(x)=\frac{96L^{3}}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\left[(-1)^{n}3+\frac{4}{(2n-1)\pi}\right]\cos\frac{(2n-1)\pi x}{2L}$$

47. $$C_{M}(x)=\frac{96L^{3}}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\left[(-1)^{n}5+\frac{8}{(2n-1)\pi}\right]\cos\frac{(2n-1)\pi x}{2L}$$

48. $$C_{M}(x)=-\frac{384L^{4}}{\pi ^{4}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{4}}\left[1+\frac{(-1)^{n}4}{(2n-1)\pi}\right]\cos\frac{(2n-1)\pi x}{2L}$$

49. $$C_{M}(x)=-\frac{768L^{4}}{\pi ^{4}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{4}}\left[ 1+\frac{(-1)^{n}2}{(2n-1)\pi}\right]\cos\frac{(2n-1)\pi x}{2L}$$

51. $$S_{M}(x)=\frac{32L^{2}}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\sin\frac{(2n-1)\pi x}{2L}$$

52. $$S_{M}(x)=-\frac{96L^{3}}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\left[1+(-1)^{n}\frac{4}{(2n-1)\pi}\right]\sin\frac{(2n-1)\pi x}{2L}$$

53. $$S_{M}(x)=\frac{96L^{3}}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\left[1+(-1)^{n}\frac{2}{(2n-1)\pi}\right]\sin\frac{(2n-1)\pi x}{2L}$$

54. $$S_{M}(x)=\frac{192L^{3}}{\pi ^{4}}\sum_{n=1}^{\infty}\frac{(-1)^{n}}{(2n-1)^{4}}\sin\frac{(2n-1)\pi x}{2L}$$

55. $$S_{M}(x)=\frac{1536L^{4}}{\pi ^{4}}\sum_{n=1}^{\infty}\frac{1}{(2n-1)^{4}}\left[(-1)^{n}+\frac{3}{(2n-1)\pi}\right]\sin\frac{(2n-1)\pi x}{2L}$$

56. $$S_{M}(x)=\frac{384L^{4}}{\pi ^{4}}\sum_{n=1}^{\infty}\frac{1}{(2n-1)^{4}}\left[ (-1)^{n}+\frac{4}{(2n-1)\pi}\right]\sin\frac{(2n-1)\pi x}{2L}$$

This page titled 11.11: A.11.3- Section 11.3 Answers is shared under a CC BY-NC-SA 3.0 license and was authored, remixed, and/or curated by William F. Trench.